Strategi Kepala Sekolah Untuk Meningkatkan Kinerja Guru di SMPN 29 Satu Atap Malaka Maros - Rosmini, Rosmini; Bunyamin, Andi; Sudarmono R, Muh Aidil; Raehana, Syarifa; Mustamin, Mustamin (LP2M Universitas Islam Ahmad Dahlan, 2025)
The role of the principal is very important in improving the quality of education through improving teacher performance. Therefore, this study uses a qualitative approach (case study) at SMPN 29 Satu Atap Malaka, Maros Regency, to describe the principal's strategy in achieving these goals. Data were collected through observation, in-depth interviews, and documentation. The findings of the study show how well the principal's plan succeeded in improving teacher performance. The approach succeeded in improving teacher discipline, creativity, and responsibility by offering incentives and rewards, supervision and evaluation, professional development, and a supportive work environment. This study concluded that the three key elements of transformative principal leadership, effective interpersonal communication, and cooperative support from all school stakeholders have a significant impact on the success of implementing teacher performance improvement techniques. These results have significant consequences for the creation of a school leadership model that focuses on improving teacher performance sustainably.